Risk Management Implementation Requirements in Riyadh Public Schools - Almufeez, Khawla Abdullah (Dirasat: Educational Sciences, 2023)
Objectives: The study aims to identify the degree of approval of Riyadh City public school principals with the needed requirements for risk management implementation. The study also investigates the effect of sample study changes (gender, years of service) on these requirements. Methods: A descriptive research approach using a questionnaire was pursued to answer the requirements for the use of risk management in general education schools. A sample of 361 Riyadh public school principals was randomly selected and classified utilizing the Likert-quinquennial scale. Specifically, the arithmetic average was divided up into the following scale categories: very weak approval (1-1.8), weak approval (1.81-2.6), medium approval (2.61-3.4), high approval (3.41-4.2), and very high approval (4.21-5). Results: The study found that the sample believed that general education schools in Riyadh have a "medium" level of readiness for implementing risk management across various areas. The highest-rated area was "technical requirements," followed by "management and administration requirements," and finally, "physical and human requirements." Gender differences were significant, favoring females in their perception of technical requirements. Additionally, teachers with less than five years of experience differed significantly from those with more experience in their views on material, human, and technical requirements for risk management. Conclusions: The study recommends that risk management training programs be designed, communication channels are strengthened to raise awareness and support participation in decision-making, and funding sources be employed to provide risk protection tools and equipment.